Development of Interactive Multimedia Learning Materials based on National Income for High School Students - Kurniasandi, Zordi; H Matsum, Junaidi; Warneri, Warneri; Wulandari, Novia Dian Kartika (International Journal of Learning and Instruction (IJLI), 2024)
The developed interactive PowerPoint media utilizes hyperlink features, thus making the learning process more interactive. The PowerPoint media produced represents an innovative product derived from previously used media at SMAN 2 Sukadana Kayongutara. The aim of this study is to determine the feasibility of interactive PowerPoint media. The research stages include the preparation of interactive PowerPoint media, validation testing of the interactive PowerPoint media, and refinement of the interactive PowerPoint according to the suggestions provided by two validators. The aspects assessed in this research are content, media, and language. The feasibility of the interactive PowerPoint media was analyzed using the Gregory formula. The validation results indicate that each aspect"”content, media, and language"”received an average score of 1.00, categorizing them as highly valid. It is concluded that the interactive PowerPoint media is suitable for use as a learning medium for the national income topic in the eleventh-grade curriculum.  Keywords: Interactive Powerpoint Media, Validation, Aspect